Effect of Ultraviolet Exposure on Impact Resistance of Ophthalmic Lenses. Issue 12 (December 2015) - Chou, B. Ralph; Dain, Stephen J.; Cheng, Brian B.
ABSTRACT: Purpose: To investigate the effect of ultraviolet radiation (UVR) on the impact resistance of organic ophthalmic lens materials. Methods: Plano power CR39, Phoenix, Trilogy, and polycarbonate lenses with various scratch-resistant (SR) and/or antireflection (AR) coatings were obtained in batches of 40 units. All lenses had a nominal thickness of 2 mm. Half of each batch was conditioned following the European Standard EN 168 protocol for the test of resistance to UVR (exposed group). The remaining lenses comprised an unexposed group for that combination of lens substrate and coating treatment. Each group was subjected to ballistic impact with 6-mm steel balls following the ZEST protocol to determine its mean breakage velocity. The difference in mean breakage velocity between exposed and unexposed groups of each combination of lens substrate and coating was assessed for statistical significance. Results: Exposed uncoated CR39 showed a reduction in fracture velocity of 10.3 m/s whereas CR39 with ultra hard coat had a reduction of 3.5 m/s and CR39 with AR and SR coating had a reduction of 4.1 m/s. Scratch-resistant coated Phoenix had a reduction of 4.8 m/s whereas AR-coated Phoenix had a reduction of 3.7 m/s. The corresponding reductions for Trilogy were 3.9 and 17.8 m/s. All differences were significant at the p level of less than 0.05. Although we were unable to break unexposed SR-coated polycarbonate lenses with our test apparatus, exposed SR-coated polycarbonate had a mean breakage velocity of 142 m/s. Conclusions: Our data suggest that extended UVR exposure causes a significant reduction in the impact resistance of the ophthalmic lens substrates commonly used for occupational eye protectors. Protective lenses that have been exposed to high levels of UVR for extended periods should be replaced regularly to maintain optimal impact protection, even if they do not show visible damage owing to wear and tear.